Time-varying transmission efficiency of China's monetary policy. Issue 1 (2nd January 2019) - Ge, Tingting
ABSTRACT: This paper tries to investigate the time-varying characteristics of China's monetary policy transmission from the impulse response evidence of both open-economy DSGE model and TVP-VAR model. We find that the transmission efficiency of price-based monetary policy has significantly improved over the sample period, while quantity-based monetary policy is weakening. The resume of exchange reform in 2010 also strengthens the exchange rate channel especially in terms of price-based monetary policy. Combining with the evidence from DSGE model underlines the importance of further interest rate liberalization and price-based monetary policy Taylor rule should also consider the exchange rate stability.